2006
DOI: 10.1016/j.cemconres.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Opal-A rich additives used in ancient lime mortars

Abstract: Ancient stone and brick masonry mortars from three monuments in Konya, Central Anatolia dated to the Anatolian Selçuk Period (12th and 13th centuries AD) were examined for their raw material composition and durability characteristics to understand some characteristics of medieval mortar technology.Optical microscopy, XRD, SEM, EDX, FTIR and TGA analyses revealed that the mortars contained high percentage of lime binder totally carbonated into micritic calcite. Coarse and medium aggregates were mainly composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…general, it has been observed that Fa has a positive contribution to the reduction of the water absorption rates.When the obtained results are compared with the original historical building mortars in the literature; It has been observed that Byzantine roman mortars which have a water absorption rate of 18-23% and Ottoman mortars with a water absorption rate of 10-24% are closer to the values of Fa + zeolite mixtures of this study with a water absorption rate of 16-29%(36).…”
supporting
confidence: 59%
“…general, it has been observed that Fa has a positive contribution to the reduction of the water absorption rates.When the obtained results are compared with the original historical building mortars in the literature; It has been observed that Byzantine roman mortars which have a water absorption rate of 18-23% and Ottoman mortars with a water absorption rate of 10-24% are closer to the values of Fa + zeolite mixtures of this study with a water absorption rate of 16-29%(36).…”
supporting
confidence: 59%
“…Mortars with lime as binder have been used throughout the past millennia for the construction and surface finish of buildings [1][2][3]. It is only from the nineteenth century onwards that the use of lime mortars decreases with a rapid pace.…”
Section: Introductionmentioning
confidence: 99%
“…Lime mortar is a common inorganic material used in ancient building construction worldwide due to its excellent binding and solidification properties [4][5][6][7]. It can be modified for various purposes and performances by different additives such as fiber [8], blood [9], sticky rice [10,11], crushed brick [12], opal [13], etc. But none of these modifications helps to meet the requirements of ship use, i.e., waterproofing.…”
Section: Introductionmentioning
confidence: 99%